1995
DOI: 10.3109/02770909509082760
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Opinions on Respiratory Care: Do Doctors Fulfill Their Needs?

Abstract: To date, guidelines and consensus reports on quality care for asthma and chronic obstructive pulmonary disease (COPD) are mainly based on research and opinions of care providers. Patients' viewpoints on good medical care have rarely been studied. We designed a postal questionnaire to study the needs of patients with asthma or COPD for medical care provided by general practitioners and lung physicians. A total of 121 patients filled out the questionnaire, which included 111 items about needs. Although generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The actual reasons behind the high need for more information among the majority of our participants are not clear. A similar study in the Netherlands exploring the information needs of asthma patients also concluded that participants reported several unfulfilled needs (Koning et al 1995). However, the reasons for high informational needs might be related to weakness of medical education provided to the patient at early stages of diagnosis or the ongoing education related to, for example, acute severity of the condition or deterioration caused by aging and so forth.…”
Section: Discussionmentioning
confidence: 88%
“…The actual reasons behind the high need for more information among the majority of our participants are not clear. A similar study in the Netherlands exploring the information needs of asthma patients also concluded that participants reported several unfulfilled needs (Koning et al 1995). However, the reasons for high informational needs might be related to weakness of medical education provided to the patient at early stages of diagnosis or the ongoing education related to, for example, acute severity of the condition or deterioration caused by aging and so forth.…”
Section: Discussionmentioning
confidence: 88%
“…An expert panel of the Italian Society of Respiratory Medicine (SIMeR) developed a survey containing 28 multiple-choice questions on the basis of literature analysis (13)(14)(15)(16)(17)(18). The intent of the survey was to explore the physicians' personal experiences regarding asthma management and their perceptions of asthma patients' needs.…”
Section: Physician Survey: Tool Developmentmentioning
confidence: 99%
“…While effective management of symptoms through appropriate use of medication is vital, education and information play a significant role, with tailored information being shown to be highly effective in asthma care 45 Asthma patients report unmet information needs and are generally keen to participate in the decision-making process 6. A disconnection has been reported between patients and healthcare providers views about what patients need to know 7…”
Section: Introductionmentioning
confidence: 99%